(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
In order to study the behaviour of Apis mellifera L. by gathering pollen when orchards bloom, observations were planned of crops in northem Italy, where Malus domestica, Pyrus communis, Prunus spp., Rubus spp. bloom simultaneously with many other wild flowers. Samples of pollen gathered from bees were periodically removed by traps in various localities from the beginning of spring to June and submitted to analysis. The results of analysis show the botanica! species and their respective percentages. The data proved that the bees forage frequently anemophilous and entomophilous blossoms, which are near orchards and often neglect crops. However there was enough pollination of each crop both for the presence of many apiaries in the environment and for the frequent flights of nectar-collecting bees to flowers. The quantities of pollen gathered from some experimental colonies indicate that annual totals are similar for each locality but the daily quantities are very variable, depending on weather conditions.